Downscaling the ERA5 reanalysis for 'Hurricane' Debbie (1961): evidence of both cold‐conveyor belt and sting jets. (4th September 2021) - Smart, David; Graham, Edward
Abstract : We report the results of a downscaling simulation of Hurricane Debbie (1961) in its extratropical transition phase and as a severe extratropical storm in the Northeast Atlantic over the mainland of Ireland and Northern Ireland. The Weather Research and Forecasting model was initialised with ERA5 reanalysis data. The results provide evidence of the presence of two types of low‐level jet during the most severe phase of the storm.